2019
DOI: 10.1002/vjch.2019000141
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of novel poly[4‐phenyl‐3‐(thiophen‐3‐ylmethyl)‐1H‐1,2,4‐triazole‐5(4H)‐thione]

Abstract: By the oxidative coupling polymerization, a new polythiophene containing 1,2,4‐triazole heterocyclic group was synthesized in chloroform solvent using iron(III) chloride as an oxidant catalyst. Analyses of infrared (IR) and ultraviolet–visible (UV‐Vis) spectra confirmed that the polymerization reaction took place and the absorption band at 469 nm characterized for π–π* transition in the conjugated polymer. Morphology and surface properties of the polymer were studied by field emission scanning electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…The crystal and molecular structures of C 13 H 8 OS–H, C 13 H 8 OS–Br, C 13 H 8 OS–OH, C 13 H 8 OS–OCH 3 , and C 13 H 8 OS–OC 2 H 5 were characterized by X-ray diffraction. We showed that the chemical polymerization of monomers C 13 H 8 OS–FeCl 3 in chloroform had been performed, as recently reported [ 48 , 49 , 50 , 51 ]. The obtained results show that the bonding lengths between atoms 1 and 2 are: C–C with Br (1.33 Å), OH (1.33 Å), OCH 3 (1.33 Å), and OC 2 H 5 (1.32 Å); as well as C–O with Br (1.22 Å), OH (1.23 Å), OCH 3 (1.23 Å), and OC 2 H 5 (1.22 Å) [ 47 ].…”
Section: Introductionsupporting
confidence: 77%
“…The crystal and molecular structures of C 13 H 8 OS–H, C 13 H 8 OS–Br, C 13 H 8 OS–OH, C 13 H 8 OS–OCH 3 , and C 13 H 8 OS–OC 2 H 5 were characterized by X-ray diffraction. We showed that the chemical polymerization of monomers C 13 H 8 OS–FeCl 3 in chloroform had been performed, as recently reported [ 48 , 49 , 50 , 51 ]. The obtained results show that the bonding lengths between atoms 1 and 2 are: C–C with Br (1.33 Å), OH (1.33 Å), OCH 3 (1.33 Å), and OC 2 H 5 (1.32 Å); as well as C–O with Br (1.22 Å), OH (1.23 Å), OCH 3 (1.23 Å), and OC 2 H 5 (1.22 Å) [ 47 ].…”
Section: Introductionsupporting
confidence: 77%